Kinetic origin of hysteresis and the strongly enhanced reversible barocaloric effect by regulating the atomic coordination environment - Zi-Bing Yu; Hou-Bo Zhou; Feng-Xia Hu; Jian-Tao Wang; Fei-Ran Shen; Lun-Hua He; Zheng-Ying Tian; Yi-Hong Gao; Bing-Jie Wang; Yuan Lin; Yue Kan; Jing Wang; et al. (NPG Asia Materials)
Abstract Hysteresis is an inherent property of first-order transition materials that poses challenges for solid-state refrigeration applications. Extensive research has been conducted, but the intrinsic origins of hysteresis remain poorly understood. Here, we report a study of the kinetic origin of hysteresis and the enhanced barocaloric effect (BCE) in MnCoGe-based alloys with ~2% nonmagnetic In atoms. First-principles calculations demonstrate that substituting In atoms at Ge sites rather than Co sites results in a lower energy barrier, indicating a narrower hysteresis for the former. Combining neutron powder diffraction (NPD) with magnetic and calorimetric measurements completely verified the theoretical prediction. Electron local function (ELF) calculations further reveal the atomic coordination origin of regulated hysteresis due to weaker Co–Ge bonds when In atoms replace Ge, which is opposite to Co sites. Moreover, we experimentally investigate the BCE and find that although MnCo(Ge0.98In0.02) has a lower barocaloric entropy change ΔSP than does Mn(Co0.98In0.02)Ge, the reversible ΔSrev of the former is advantageous owing to a smaller hysteresis. The maximum ΔSrev of MnCo(Ge0.98In0.02) is 1.7 times greater than that of Mn(Co0.98In0.02)Ge. These results reveal the atomic-scale mechanism regulating hysteresis and provide insights into tailoring the functional properties of novel caloric refrigeration materials.